Demographics and (Equal?) Voice: Assessing Participation in Online Deliberative Sessions. (February 2021) - Kennedy, Ryan; Sokhey, Anand E; Abernathy, Claire; Esterling, Kevin M; Lazer, David MJ; Lee, Amy; Minozzi, William; Neblo, Michael A
Critics of deliberative democracy have worried that deliberation may mirror (or even exacerbate) inequalities in participation across categories such as gender, race, and age. Accordingly, we investigate the potential for technology and design to ameliorate these concerns, looking at the extent to which online deliberative sessions facilitate inclusive participation. In a large study of online deliberation (over 1600 participants nested in hundreds of online sessions), we examine differences in the amount and nature of participation across demographic categories, as well as the effect of forum characteristics on such differences. Though our results are mixed, we read them with cautious optimism: the online format is not immune to inequalities in participation and satisfaction, but we do not observe differences across some demographics, and most observed differences are substantively minor. Moreover, features of online deliberation environments show promise for addressing some of the problems plaguing in-person designs.